2012
DOI: 10.1007/s00125-012-2516-2
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant activation of liver X receptors impairs pancreatic beta cell function through upregulation of sterol regulatory element-binding protein 1c in mouse islets and rodent cell lines

Abstract: Aims/hypothesis Liver X receptors (LXR) are important transcriptional regulators of lipid and glucose metabolism. Our previous report demonstrated that LXR activation inhibited pancreatic beta cell proliferation through cell cycle arrest. Here we explore the role of LXR activation in beta cell insulin secretion and the underlying mechanism that might be involved. Methods Mouse pancreatic islets or insulin-secreting MIN6 cells were exposed to the LXR agonist, T0901317, and insulin secretion, glucose and fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
3
16
0
Order By: Relevance
“…The role of LXR in regulating glucose tolerance in vivo is still somewhat controversial [26]. The LXR agonist used in this study was reported to improve glycaemic control in db/db mice and in Zucker fatty rats [27,28], but worsened glycaemic control in normal C57BL/6 mice [29]. Consistent with the latter finding, LXR-deficient mice had better glycaemic control when fed a western-style diet [30].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The role of LXR in regulating glucose tolerance in vivo is still somewhat controversial [26]. The LXR agonist used in this study was reported to improve glycaemic control in db/db mice and in Zucker fatty rats [27,28], but worsened glycaemic control in normal C57BL/6 mice [29]. Consistent with the latter finding, LXR-deficient mice had better glycaemic control when fed a western-style diet [30].…”
Section: Discussionsupporting
confidence: 79%
“…The discrepancy between these findings is difficult to explain, but the different dietary interventions used in each study might contribute to these differences because hepatic LXR is activated by the dietary cholesterol content in a dose-dependent manner [31]. In the present study, the FLS mice were fed a normal diet with a low cholesterol content, similar to the conditions used in an earlier report [29]. Under these conditions, LXR activation might overcome BAR-mediated suppression of LXR activity.…”
Section: Discussionmentioning
confidence: 75%
“…The intracellular cholesterol transport protein Npc1, genetically associated with risk of obesity in humans, may also play a role in insulin secretion [56]. LXR alpha, a receptor for cholesterol-related compounds, is important for insulin secretion in vitro and in vivo by altering glucose metabolism, ATP production and calcium channel flux; modulating its activity deregulated lipid metabolism via SREBP [57]. …”
Section: Intracellular Mechanisms Of Lipotoxicitymentioning
confidence: 99%
“…In these studies, positive outcomes are primarily mediated by inhibition of gluconeogenesis and limitation of glucose output from the liver; however, recent studies using LXR-knockout mice have demonstrated opposing results [8][9]. Furthermore, Meng et al [10] has shown decreased β cell glucose sensitivity and insulin secretion in response to LXR activation in vitro and deterioration of glucose tolerance in vivo manifested as suppressed insulin secretion in response to glucose injection. Another study has also demonstrated that LXR activation downregulated insulin-stimulated glucose uptake in human adipocytes from overweight individuals, which could be due to transcriptional suppression of several insulin signaling genes [11].…”
Section: Introductionmentioning
confidence: 99%